MANAGEMENT OF ENDOCRINE DISEASE: Klinefelter syndrome, cardiovascular system, and thromboembolic disease: review of literature and clinical perspectives. Issue 1 (July 2016) - Salzano, Andrea; Arcopinto, Michele; Marra, Alberto M; Bobbio, Emanuele; Esposito, Daniela; Accardo, Giacomo; Giallauria, Francesco; Bossone, Eduardo; Vigorito, Carlo; Lenzi, Andrea; Pasquali, Daniela; Isidori, Andrea M; et al.
Abstract : Klinefelter syndrome (KS) is the most frequently occurring sex chromosomal aberration in males, with an incidence of about 1 in 500–700 newborns. Data acquired from large registry-based studies revealed an increase in mortality rates among KS patients when compared with mortality rates among the general population. Among all causes of death, metabolic, cardiovascular, and hemostatic complication seem to play a pivotal role. KS is associated, as are other chromosomal pathologies and genetic diseases, with cardiac congenital anomalies that contribute to the increase in mortality. The aim of the current study was to systematically review the relationships between KS and the cardiovascular system and hemostatic balance. In summary, patients with KS display an increased cardiovascular risk profile, characterized by increased prevalence of metabolic abnormalities including Diabetes mellitus (DM), dyslipidemia, and alterations in biomarkers of cardiovascular disease. KS does not, however, appear to be associated with arterial hypertension. Moreover, KS patients are characterized by subclinical abnormalities in left ventricular (LV) systolic and diastolic function and endothelial function, which, when associated with chronotropic incompetence may led to reduced cardiopulmonary performance. KS patients appear to be at a higher risk for cardiovascular disease, attributing to an increased risk of thromboembolic events with a high prevalence of recurrent venous ulcers, venous insufficiency, recurrent venous and arterial thromboembolism with higher risk of deep venous thrombosis or pulmonary embolism. It appears that cardiovascular involvement in KS is mainly due to chromosomal abnormalities rather than solely on low serum testosterone levels. On the basis of evidence acquisition and authors' own experience, a flowchart addressing the management of cardiovascular function and prognosis of KS patients has been developed for clinical use.